Study of Communication-Media Strategies to Encourage Citizens to Segregate Waste at Source (Case Study: City of Tabriz) - Salmani , Roya; Samadi, Mehran (Digital Transformation and Administration Innovation, 2026)
The present study was designed to investigate effective communication and media strategies to encourage citizens of Tabriz to segregate waste at the source. Employing a mixed-methods approach, the research explored various dimensions of behavior and awareness regarding waste management. A sample of 456 individuals over the age of 15 residing in the ten districts of Tabriz municipality was selected using a multistage cluster sampling method based on Cochran's formula. Initially, each city district was divided into neighborhoods, neighborhoods were randomly selected, and finally, participants voluntarily completed questionnaires. Quantitative results indicated a low level of awareness among citizens regarding the environmental and economic consequences of non-segregation, alongside a lack of social participation. These findings led the research towards a qualitative phase involving semi-structured interviews with 15 experts in media, urban management, and environmental fields. Qualitative data were coded through thematic analysis, extracting a network of primary and secondary themes of communication strategies. Effective strategies included continuous education, utilization of traditional and digital media, cultural campaigns, environmental advertising, and leveraging community networks. Based on the theoretical framework of the Theory of Planned Behavior and the Health Belief Model, a combination of local-social education and financial incentives emerged as key to enhancing citizen participation in Tabriz's waste management. The study provides practical solutions while emphasizing the pivotal role of media development and civic education in achieving sustainable urban waste management.